PANDANGAN IBNU TAIMIYAH PERSPEKTIF EKONOMI ISLAM - Adim, Abd (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Islam is the most perfect religion from other religions. It is called perfect because Islam is the complementary religion of the previous religions and its syari'at regulates all aspects of life, both those that are aqidah worship and Maliyah both horizontally and vertically and Islam is also rahmatan lilalamin. In the norm of maliyah, Islam regulates all forms of human behavior in dealing with others to meet the needs of life in the world. This includes the principles governing the market and mechanisms. In the realm of Islamic economic thought, there is a scholar, Ibn Taymiyyah, who has discussed a lot about economics, including his opinion on markets, prices, justice, economic principles and other economic thoughts. Every economic activity must contain an element of benefit and not abuse himself and others, so that economic activities can create welfare for the community evenly.